Trophic State Index to assess aquatic ecosystem health - Sarkar, Soma Das; Gogoi, Pranab; Sarkar, U K; Ghosh, Bandana Das; Mishal, P (Indian Farming, 2019)
Trophic state index is a monitoring tool to assess the state (oligotrophy, mesotrophy, eutrophy and hypereutrophy) of an aquatic ecosystem which indeed serves as baseline for measuring biological integrity and interface between human and water environment. This tool is comprehensively used for formulating climatic model base which helps in developing rehabilitation and restoration strategies of the various aquatic ecosystems. Thus, it is effective for climate researchers for use of lentic and lotic environment in the long run.